2003
DOI: 10.2116/analsci.19.1355
|View full text |Cite
|
Sign up to set email alerts
|

Piezo Electric Sensor for Endocrine-Disrupting Chemicals Using Receptor–co-factor Interaction

Abstract: The hER is a ligand-dependent transactivator that belongs to a large superfamily of nuclear receptors. These family proteins bind various small hydrophobic ligands including the steroid hormones, thyroid hormone, vitamin D, and the retinoids for the activation. The hERs constantly shuttle between the cellular nucleus and the cytoplasm, but under steady-state conditions they are predominantly found in the nucleus.In the inactive state, hER is present as a complex with a heat shock protein (hsp90). If the ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Other examples for small molecule detection, in particular environmental contaminants include petroleum hydrocarbons (Fahnrich et al, 2002;Applebee et al, 2004), Cr 6þ , Cr 3þ , Cd 3þ , Cu 2þ and other ions (Howie and Hoagland, 2002;Mirmohseni and Oladegaragoze, 2002;Tani and Umezawa, 2003;Sung and Shih, 2005), estrogenic compounds (Murata et al, 2003;Luck et al, 2004), aliphatic amines (Mirmohseni and Oladegaragoze, 2003), phenol (Mirmohseni and Oladegaragoze, 2004), sulfur dioxide (Palenzuela et al, 2005), NO x (Seh et al, 2005), enantiomers , pesticides , doxorubicin (Serpe et al, 2005), cholesterol (Ram et al, 2001), limonene (Fietzek et al, 2001), alcohols (Loergen et al, 2005), dioxins Kurosawa et al, 2003) and cisplatinum drugs .…”
Section: Direct Receptor-small Molecule Interactionmentioning
confidence: 99%
“…Other examples for small molecule detection, in particular environmental contaminants include petroleum hydrocarbons (Fahnrich et al, 2002;Applebee et al, 2004), Cr 6þ , Cr 3þ , Cd 3þ , Cu 2þ and other ions (Howie and Hoagland, 2002;Mirmohseni and Oladegaragoze, 2002;Tani and Umezawa, 2003;Sung and Shih, 2005), estrogenic compounds (Murata et al, 2003;Luck et al, 2004), aliphatic amines (Mirmohseni and Oladegaragoze, 2003), phenol (Mirmohseni and Oladegaragoze, 2004), sulfur dioxide (Palenzuela et al, 2005), NO x (Seh et al, 2005), enantiomers , pesticides , doxorubicin (Serpe et al, 2005), cholesterol (Ram et al, 2001), limonene (Fietzek et al, 2001), alcohols (Loergen et al, 2005), dioxins Kurosawa et al, 2003) and cisplatinum drugs .…”
Section: Direct Receptor-small Molecule Interactionmentioning
confidence: 99%
“…For example, self‐assembled layers of long‐chain alkanethiols have been employed as a foundation layer for gold‐electrode fabrication to reduce nonspecific adsorption and surface denaturation of proteins and to improve the reusability and stability of PZ biosensor chips (18 − 21). Moreover, PZ biosensors prepared by hydrogel coating (5, 19, 21−25) as well as those indirectly prepared by directional or functional immobilization of biomolecules using affinity ligands, such as metal chelators (21, 26), protein A (19, 20, 22), and (strept)avidin (3−5), have shown increased activity, binding capacity, and sensitivity. Recent studies have also demonstrated that the fabrication using a combination of alkanethiols, hydrogel, and affinity ligands appears to be the most promising technology for PZ biosensor preparations (5, 19, 21).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they identified the three peptides αβ/I, αβ/II, and αβ/III, which have selective affinity for the conformation of the apo form of the ER-LBD and the conformations induced by estradiol and the antagonist 4-hydroxytamoxifen, respectively (Figure ). Previous studies using ELISA techniques, ,,, a piezoresistive canteliver, quartz crystal microbalance, or cyclic voltammetry , have successfully shown that ER agonists and antagonists can be detected and, in the setups using ELISA and cantilevers, distinguished through the selective binding of CS peptides to the ER.…”
mentioning
confidence: 99%